The First Ten Years Of The Constitutional Court Of Indonesia: The Establishment Of The Principle Of Equality And The Prohibition Of Discrimination - Eddyono, Luthfi Widagdo (The Constitutional Court of the Republic of Indonesia, 2015)
As a very fundamental principle of the 1945 Constitution, principle of equality and prohibition of discrimination does not only serve as the basic norm, but most importantly it also have functions as the source of morality for the constitution, as well as for the practices of politics, socio-economics and law in Indonesia. This article will pick and analyses significant and landmark decisions that made by the Constitutional Court of Indonesia in its 10 years existence related to principle of equality and prohibition of discrimination to understand how the Court interpreted the constitution and which principle that usually used by the Court in its practices. The result is based on its 10 years of experiences, The Constitutional Court of Indonesia have gave tremendous contribution for the protection of human rights and the advancement of democracy and nomocracy in Indonesia, especially for the establishment of the principle of equality and Â the prohibition of discrimination based on 1945 Constitution and the principle of proportionality.